Factors Affecting Gastrointestinal Disorders in Patients Undergoing Regular Hemodialysis - Pasaribu, Rosarina; Muzasti, Riri Andri (Sumatera Medical Journal, 2020)
Background: Chronic Kidney Disease (CKD) is an immense health issue. The prevalence is increasing each year worldwide, including Indonesia. Consistent with this trend, the prevalence of hemodialysis (HD) as a therapy is also increasing. CKD as well as HD often result in some complications, one being gastrointestinal disorders. Many factors are correlated with the incidence of gastrointestinal disorders in CKD patients undergoing HD. Objective: This research is held to observe the factors affecting gastrointestinal disorders in regular HD patients. Method: This is an observational analytical research with cross-sectional study at RS Khusus Ginjal Rasyida Medan. The datas used in the research are primary datas, obtained from Gastrointestinal Symptoms Rating Scale (GSRS) questionnaire to assess severity of gastrointestnal disorders in HD patients, and secondary datas, obtained from medical records of age, smoking history, use of aspirin, HD duration, BUN, and Kt/V (as a parameter of HD adequacy). Then the datas are analyzed univariately, bivariately, and mutivariately using biner logistic regression model. It is considered significant if the obtained p value is <0,05 (p<0,05). Result: All patients (100%) suffer from gastrointestinal disorders, with the most common being mild ones (67,1%). Final multivariate analysis shows that the duration of HD, BUN level, and Kt/V are significantly correlated with worsening gastrointestinal disorders (OR:14,157 ,95%CI 2,851 ± 71,183, p=0,001; OR: 8,352, 95%CI 0,914 ± 76,344, p= 0,060; OR:8,219 ,95%CI 0,893 ± 75,674, p= 0,063). Conclusion: The duration of HD, BUN level, and Kt/V are correlated with worsening gastrointestinal disorders in HD patients.